Notes on sufficient conditions for a graph to be Hamiltonian - Michael Joseph Paul; Carmen Baytan Shershin; Anthony Connors Shershin (International Journal of Mathematics and Mathematical Sciences)
The first part of this paper deals with an extension of Dirac's Theorem to directed graphs. It is related to a result often referred to as the Ghouila-Houri Theorem. Here we show that the requirement of being strongly connected in the hypothesis of the Ghouila-Houri Theorem is redundant.